Three-dimensional modeling and visualization of the cochlea on the Internet. - Yoo, S.K (IEEE Transactions on information technology in biomedicine)
3D modeling and visualization of the cochlea using the World Wide Web (WWW) is an effective way of sharing anatomic information for cochlear implantation over the Internet, particularly for morphometry-based research and resident training in otolaryngology and neuroradiology. In this paper, 3D modeling, visualization and animation techniques are integrated in an interactive and platform-independent manner and implemented over the WWW. L.T. Cohen et al.'s (1996) template shape with mean cross-sectional areas of the human cochlea is extended into a 3D geometrical model. Also, spiral computer tomography data of a patient's cochlea is digitally segmented and geometrically represented. The cochlear electrode array is synthesized according to its specification. Then, cochlear implantation is animated with both idealized and real cochlear models. The insertion length, angular position and characteristic frequency of individual electrodes are estimated online during the virtual insertion. The optimization of the processing parameters is done to demonstrate the feasibility of this technology for clinical applications.